EVALUASI KLINIS DAN LABORATORIS PASIEN ANJING YANG DIDUGA MENDERITA DERMATOFITOSIS DI WILAYAH YOGYAKARTA - , GERSON YOHANIS IMANUEL SAKAN ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Dermatophytosis is a zoonotic disease caused by one or more species of fungi from the group of dermatophytes. The cases of dermatophytosis in dogs in Yogyakarta encountered by veterinary practitioners, but the formal information about dermatophytosis is limited so the diagnosis and therapy of this disease is not applied optimally. The objective is the study is to evaluate the dermatophytosis in dog based on clinical sign, phenotypes identification of dermatophytes and sensitivity test of dermatophytes againts antifungal drugs. The sample used in this study were 50 patients with various race and age of dogs that are clinically suspected of having dermatophytosis in a veterinary clinic in the Yogyakarta. Examination of clinical lesions and screening test with Wood's lamp made before the skin scrapings taken at the area of suspicious lesions. Dermatophytes fungi are cultivated on the medium Sabouraud's dextrose agar for further macroscopic and microscopic identification. Antifungal sensitivity test performed in vitro using disc diffusion method with 4 types of antifungal: griseofulvin, ketoconazole, fluconazole, and terbinafine. The results of isolation and identification of 50 samples showed: a) 18 samples of which grows with the characteristics of a suspected fungal dermatophytes, where 17 samples (34%) identified as Microsporum canis, and one sample (2%) as Trichophyton mentagrophytes, b) 27 samples (54%) showed growth characteristics of fungi other than dermatophytes and c) five samples (10%) showed no growth on the media. 18 positives sampels showed the variation of clinical lesion of dermatophytosis, whichis a combination of alopecia annular, erythema, papulae, scaly and crusty with the various spreading locations of lesions. Sensitivity test results showed all 18 isolates of dermatophytes fungi are still sensitive to all of four antifungal tested. Based on this study concluded that dermatophytosis in Yogyakarta may be found in all races and age of dogs with the cause are Microsporum canis and Trichophiton mentagrophytes, with the location of clinical lesions in various parts of the body. All of dermatophytes isolates obtained from this activity are still sensitive against to the griseofulvin, ketoconazole, fluconazole, and terbinafine antifungal.